LOIS PARKINSON ZAMORA. Beyond Individualism: Portraying Collective Selfhood in Latin America. Chicago and London: U of Chicago P, 2025. 416 pp. - Russek, Dan (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2025)
Reseña de Beyond Individualism: Portraying Collective Selfhood in Latin America de Lois Parkinson Zamora.